Expression of GBS virulence genes in high vaginal swabs of symptomatic pregnant women at Hospital Tengku Ampuan Afzan, Kuantan - Muhammad Faiz Matsuno, Aishah Sarah; Kamalullail, Nadhir Farhan; Muhamad, Ariff Aiman; Eddi, Khairul Ikhwan; Abdul Latif, Balqis Nur Aisyah; Supangat, Muhamad Haziq; Faiz, Fathul Aiman; Azmi, Asif Fikri; Mohd Ishak, Noor Fatin Nabilah; Saaidon, Nur Sakeenah; Hanizam, Nur Hannani; Ripin, Intan Nurfatihah; et al. (2021)
During pregnancy, group B streptococcus (GBS) colonization is known as one of the risk factors for preterm birth and consequently neonatal infections. Previous in-vitro experiments using human cells and in vivo animal models have portrayed the important roles of these virulence factors including hemolytic pigment (CylE), hyaluronidase (HylB), serine-rich protein (Srr) and bacterial surface adhesion of GBS (BsaB) in mediating GBS colonization and intrauterine ascending infection, leading to preterm delivery. The aim of this study is to investigate the association between mRNA expression of women and preterm delivery. GBS isolates were obtained from high vaginal swabs of pregnant women(n=40) with gestational age less than 37 weeks and symptoms including preterm labour, preterm premature rupture of membrane (pPROM), vaginal discharge and vaginal bleeding. Socio-demographic details, obstetric history and delivery outcomes of these women were also enquired. RNA was extracted from these GBS isolates and RT-qPCR was performed to determine the relative mRNA expression of GBS virulence genes including CylE,HylB, Srr and BsaB. Socio-demographic details and obstetric history were not found to be associated with the delivery outcomes of these women. Women with preterm labour and pPROM who delivered prematurely were demonstrated with higher expression of HylB and Cyl Egenes, in comparison to women with term delivery. The expression of Srr and BsaB genes were both similar between symptomatic pregnant women who had term and preterm delivery. Theseresultssuggestthatfollowingvaginalcolonization,bothCylEandHylBgenespossiblycontributetointrauterineascendinginfectionandinflammation,leading to preterm delivery in humans.Thus, hemolytic pigment and hyaluronidase may be targeted for exploratory and pre-clinical stages of vaccine development, which is a good alternative to intrapartum antibiotic prophylaxis in order to prevent neonatal GBS infections.